The preschool child in Suka Village, North Sumatera - Jane A. Kusin; H. S. R. Parlindungan Sinaga; J. Khoma; J. M. Houtkooper; U. Renqvist (Paediatrica Indonesiana, 1981)
A mixed longitudinal study on growth was carried out during one year in a group of 398 children, age 0-5 years. A sharp drop of weight and height increments were observed at age 3Â·6 months.Growth rates continued to be low until about 24 months of age, after which increments were approxiately similar to British reference data.Food intake, as published in the previous article, is not the only factor of the siluation recorded.More longitudinal studies are needed 10 assess the pattern of growth of infants and young toddlers in relation 10 dietary intake and morbidity.